Single-cell and spatial transcriptomics reveal alterations in trophoblasts at invasion sites and disturbed myometrial immune microenvironment in placenta accreta spectrum disorders - Kaiyuan Ji; Yunshan Chen; Xiuyu Pan; Lina Chen; Xiaodi Wang; Bolun Wen; Junjie Bao; Junmin Zhong; Zi Lv; Zheng Zheng; Huishu Liu (BMC, 2024)
Abstract Background Placenta accreta spectrum disorders (PAS) are a severe complication characterized by abnormal trophoblast invasion into the myometrium. The underlying mechanisms of PAS involve a complex interplay of various cell types and molecular pathways. Despite its significance, both the characteristics and intricate mechanisms of this condition remain poorly understood. Methods Spatial transcriptomics (ST) and single-cell RNA sequencing (scRNA-seq), were performed on the tissue samples from four PAS patients, including invasive tissues (ST, n = 3; scRNA-seq, n = 4), non-invasive normal placenta samples (ST, n = 1; scRNA-seq, n = 2). Three healthy term pregnant women provided normal myometrium samples (ST, n = 1; scRNA-seq, n = 2). ST analysis characterized the spatial expression landscape, and scRNA-seq was used to identify specific cellular components in PAS. Immunofluorescence staining was conducted to validate the findings. Results ST slices distinctly showed the myometrium in PAS was invaded by three subpopulations of trophoblast cells, extravillous trophoblast cells, cytotrophoblasts, and syncytiotrophoblasts, especially extravillous trophoblast cells. The pathways enriched by genes in trophoblasts, smooth muscle cells (SMC), and immune cells of PAS were mainly associated with immune and inflammation. We identified elevated expression of the angiogenesis-stimulating gene PTK2, alongside the cell proliferation-enhancing gene EGFR, within the trophoblasts of PAS group. Trophoblasts mainly contributed the enhancement of HLA-G and EBI3 signaling, which is crucial in establishing immune escape. Meanwhile, SMC regions in PAS exhibited upregulation of immunomodulatory markers such as CD274, HAVCR2, and IDO1, with CD274 expression experimentally verified to be increased in the invasive SMC areas of the PAS group. Conclusions This study provided information of cellular composition and spatial organization in PAS at single-cell and spatial level. The dysregulated expression of genes in PAS revealed a complex interplay between enhanced immune escape in trophoblasts and immune tolerance in SMCs during invasion in PAS. These findings will enhance our understanding of PAS pathogenesis for developing potential therapeutic strategies.